2022
DOI: 10.7717/peerj-cs.986
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on machine learning models for online learning and examination systems

Abstract: Examinations or assessments play a vital role in every student’s life; they determine their future and career paths. The COVID pandemic has left adverse impacts in all areas, including the academic field. The regularized classroom learning and face-to-face real-time examinations were not feasible to avoid widespread infection and ensure safety. During these desperate times, technological advancements stepped in to aid students in continuing their education without any academic breaks. Machine learning is a key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 110 publications
0
14
0
Order By: Relevance
“…Its operation strategy is to retain the best individual, prevent the emergence of local optimal solution, and adhere to the elite retention strategy. The function of selecting operators in the genetic algorithm is to avoid the destruction of the Geshan gene and to improve the computational efficiency as a whole [15]. The main selection methods of the selection operator include the wheel selection method and the random selection method.…”
Section: Methodsmentioning
confidence: 99%
“…Its operation strategy is to retain the best individual, prevent the emergence of local optimal solution, and adhere to the elite retention strategy. The function of selecting operators in the genetic algorithm is to avoid the destruction of the Geshan gene and to improve the computational efficiency as a whole [15]. The main selection methods of the selection operator include the wheel selection method and the random selection method.…”
Section: Methodsmentioning
confidence: 99%
“…During the COVID-19 pandemic, some AI & ML systems entered the global educational assessment arena as an emergency measure to support exam management systems. They were used, for example, to identify at-risk students, authenticate remote students, or prevent cheating (Kaddoura et al, 2022). In England, however, the use (Huang & Wilson, 2021;Wilson et al, 2022;Wilson & Roscoe, 2020) and may improve writing skills (Nunes et al, 2022).…”
Section: Aloisimentioning
confidence: 99%
“…A review study by [29] revealed that ML such as CNN [32] can be used for EL activities such as attendance, online classes, predicting student performance, and examinations (scheduling, finding examination malpractices, authentication, and protecting), even though there are a few drawbacks such as privacy, security, and fairness.…”
Section: ML For Online Examination Supervision Purposementioning
confidence: 99%